In-group and out-group membership mediates anterior cingulate activation to social exclusion - Krill, Austen; Platek, Steven M. (Frontiers in Evolutionary Neuroscience, 2009)
Functional magnetic resonance imaging (fMRI) was employed to examine sensitivity to social exclusion in three conditions: same-race, other-race, and self-resembling faces. The anterior cingulate cortex (ACC), specifically the dorsal ACC, has been targeted as a key substrate in the physical and social pain matrix and was hypothesized to regulate activation response to various facial conditions. We show that participants demonstrated greatest ACC activation when being excluded by self-resembling and same-race faces, relative to other-race faces. Additionally, participants expressed greater distress and showed increased ACC activation as a result of exclusion in the same-race condition relative to the other-race condition. A positive correlation between implicit racial bias and activation in the amygdala was also evident. Implicit attitude about other-race faces partly explains levels of concern about exclusion by out-group individuals. These findings suggest that individuals are more distressed and their brain (i.e. neural alarm system) responds with greater activation when being excluded by individuals whom they are more likely to share group membership with.